Results of the architectural competition in Krasnoyarsk - Yamaletdinov, Sergey (project baikal, 2023)
The article presents the winners of the open architectural competition for the development of an architectural and urban planning concept for the reconstruction of the D. A. Hvorostovsky Krasnoyarsk State Opera and Ballet Theatre built in the 1970s according to a design worked out by the architects from CNIIEP (Central Research Institute of Engineering Design) of theatre buildings and sports facilities.